Study the Consumer Information Search Behavior for Credence Goods: A Case Study of Dietary Supplements - Zhang, Yiyi (2009)
Consumer information search is not only an important section of consumer decision making, but also is valuable for marketers to better understand consumer behavior. This study attempts to investigate consumer information search behavior for credence goods, especially of dietary supplements. It describes the results from a questionnaire survey conducted online from 134 respondents, and then the data is analyzed by applying SPSS. This study mainly focuses on the determinants that affect the extent of information search, and information sources that customers mostly use and rely on. It reveals that for customers, reduce risk, become more confident, saving costs and financial cost are the determinants that influence the extent of searching information about dietary supplements, while it does not obviously testify ability to search and situation factor are the factors that affect information search. Besides, when customers are searching information about dietary supplements, they usually adopt much information generated from interpersonal source, personal source and advertisements. While, they do not prefer to employ information coming from the Internet and personal selling. Additionally, personal source, interpersonal source and neutral source are the most reliable ones that customers consider when they are searching related information about dietary supplements.